1986
DOI: 10.1111/j.1442-9071.1986.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vicryl Tie Technique for Inserting a Draining Implant in the Treatment of Secondary Glaucoma

Abstract: We have reviously described surgical techni ues for draining severe cases of secondary glaucoma by means of% artificial implant Wherever posshe these implants have been inserted in two stagesThe modern microsurgical operation of trabeculectomy gives excellent results in selected cases of primary glaucoma. However, where glaucoma develops in young patients or is associated with trauma, aphakia, chronic uveitis, anterior segment neovascularisation or failure of a previous drainage operation, results are generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 3 publications
1
41
0
1
Order By: Relevance
“…10,13,26,29 Similar to our results, Munoz et al 26 reported an unfavorable influence of younger age on decreasing success of the procedure. In their series, patients operated after 5 years of age had a success rate of 88%, whereas those operated from birth to 2 years of age had a success rate of 68%.…”
Section: Discussionsupporting
confidence: 88%
“…10,13,26,29 Similar to our results, Munoz et al 26 reported an unfavorable influence of younger age on decreasing success of the procedure. In their series, patients operated after 5 years of age had a success rate of 88%, whereas those operated from birth to 2 years of age had a success rate of 68%.…”
Section: Discussionsupporting
confidence: 88%
“…In no case did formed vitreous occlude the tube. In 12 eyes (eyes 8,9,17,18,26,27,28,31,33,34,35,36) the peak IOP during the postoperative period of ocular hypertension was higher than it had been before operation, and in seven eyes (eyes 11,21,22,24,25,30,37) it was almost as high (excluding eye 3, in which pupillary block was the mechanism for the raised IOP). Visual acuity fell in five of these 19 eyes, compared with four of the remaining 16 (excluding eyes 14,19,20).…”
Section: Resultsmentioning
confidence: 95%
“…In the "two-stage' procedure the footplate is sutured into position to allow a fibrous capsule to form around the plate, and then 4-6 weeks later the tube is inserted into the anterior chamber [ 19]. In this series, the problem of excessive post operative hypotony was resolved by tying an absorbable suture around the tube, which al lowed the tube to open spontanteously about 5 weeks after surgery [20] (fig. 1).…”
Section: Discussionmentioning
confidence: 99%